The role of banking sector on economic growth in European Union and East Asia: Evidence from panel data analysis - Dehnabi, Parastou (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: This thesis empirically investigates the relationship between bank sector and economic growth whereas controlling for the effects of labour and physical capital factors in panel data estimation. Panel data which covers the period 2000 – 2010 by conducting a version of Solow Growth Model for both four European countries and four East Asia countries are used a sample in the thesis. The study mainly aims to determine whether the Bank sector and other relatively important factors stimulate the process of economic growth in the light of exogenous modelling framework by conducting the Panel Co-integration Technique. Estimated results suggest that economic growth in four European countries and four East Asia countries are in long-term equilibrium relationship; banking sector has long-term significant impact on economic growth and therefore economic growth converge to their long-term equilibrium levels through the channels of Capital and labor. However, East Asia countries have not long term and short term economic growth effect when labor and domestic credit are used whereas European countries have not long-term labor growth effect and short term money supply effect. This supports the reality that European countries are more successful in adapting banking system by using money supply as well as domestic credit than East Asia countries. However East Asia countries are more successful in adapting labor and capital policies in short-run than European countries. Therefore, authorities in East Asia countries need to adapt monetary policies effectively in order to increases efficiency through expansion in banking sectors. Keywords: Economic growth, money supply, domestic credit, capital, labor, Solow growth model, panel unit root test, panel co-integration test. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tez, bankacılık sektör etkisi ile ekonomik büyüme arasındaki ilişkiyi capital (sermaye) ve (emek) işçi değişkenlerini kullanarlak ölçer. 2000 ile 2010 yılları arasındaki Avrupa ve Uzakdoğu kıtalarında yer alan dört ülke seçilerek bankacılık sisteminin ölçümleri için panel verileri kullanılmıştır. Bu tezdeki ana amaç Solow Büyüme Modeli çerçevesinde panel birim kök ve panel eşbütünleme tekniklerini kullanıp ekonomik büyüme üzerindeki bankacılık sektörü etkilerini analiz etmektir. Ampirik bulgular hem Avrupa‟da hemde Uzakdoğu ülkelerinde uzun dönemli ilişki olduğu ve bankacılık sektörünün ekonomik büyümeyi etkilediği gözlemlenmiştir. Uzakdoğu ülkelerinde yerel sermaye ile emek piyasasının ekonomik büyüme üzerinde uzun ve kısa dönemli etkiler saptanmamıştır. Bu bulgular Avrupa ülkelerinde daha başarılı bir bankacılık sektörünün olduğunu gösteriyor. Ayrıca, Uzakdoğu emek ve sermaye piyasalarında kısa dönem için Avrupa ülkelerinden daha başarılı olduğu bulunmuştur. Dolayısıyla, uzmanlar para ve sermaye politikalarını bankacılık sektöründeki verimliliği artırabilmesi bağlamında daha iyi uygulaması gerekir. Anahtar Kelimeler: Ekonomik büyüme, para arzı, emek, sermaye, Solow Büyüme Modeli, birim kök, eşbütünleme.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Sami Fethi.
Keywords: Business Administration; Banks and banking - European Union; Banks and banking - East Asia; Economic Growth, Money Supply, Domestic Credit, Capital, Labor, Solow Growth Model, Panel unit root Test, Panel co-integration test